Investigation of isotopic signals in the unsaturated zone with the use of direct push technology and azaeotropic distillation - Kallioras, Andreas; Piepenbrink, M.; Khan, A.; Reshid, M.; Rausch, R.; Dietrich, P.; Schuth, C. (Acque Sotterranee - Italian Journal of Groundwater, 2012)
This paper contributes to the investigation of the unsaturated zone, through the application of combined field and lab techniques. The results show that direct push methods, which are considered ideal for multilevel sampling of undisturbed soil in the unsaturated zone, proved to be effective also for the consequent extraction of the pore water for further isotopic determination. This ultimate goal can be achieved thank to the application of azaetropic distillation, which has the least isotopic fractionation effects on groundwater samples.